An approach to observe fractures induced by hydraulic fracturing - Chen, Y.; Bennour, Ziad; Nagaya, Y.; Yano, S.; Suzuki, T.; Ishida, T.; Akai, T.; Takagi, S. (2015)
© 2015 by the Canadian Institute of Mining, Metallurgy & Petroleum and ISRM. It is often reported that the concept of single-plane-fracture is not sufficient to account for the productivity from shale gas/oil wells. Many researchers introduce the concept of the stimulated reservoir volume to describe observed production behaviour. However, the characteristics of the stimulated reservoir volume are not well understood. In this study, to investigate the characteristics of fractures and surrounding region induced by the hydraulic fracturing, a devised hydraulic fracturing experiment was conducted using the cylindrical shale specimens in the laboratory. Two resins were prepared as the fracturing fluid for the experiments: cyanoacrylate, an instant glue, mixed with a fluorescent paint (resin A), and methyl metaacrylate, a thermosetting acrylic resin, mixed with a fluorescent paint (resin B). These resins were able to fix within the specimen after fracturing. This is because the present study aimed to only detect fractures induced by hydraulic fracturing. Cut sections of the specimens were observed under ultraviolet light irradiation. It is expected that the hydraulically induced fractures and the surrounding regions will be detected because the induced fractures filled with the resin should emit light, while the other parts will not. The specimens, which were collected from the Kushiro Coal Mine in Hokkaido, Japan at the depth around 275 m, were roughly 85 mm in diameter, 170 mm in length, and cored normal to the sedimentary planes. An injection hole with a 10-mm diameter was drilled onto the center of the specimen parallel to the sedimentary plane to simulate hydraulic fracturing in shale gas development. The experiment was conducted under a uniaxial loading condition of 3 MPa and the fracturing fluid was injected into the sealed injection hole at a constant flow rate using a syringe pump. After the fracturing experiment, the resins were fixed in the specimens and then the cut sections were observed under ultraviolet light irradiation. As a result, the hydraulically induced fractures, which were filled with the resin, are clearly observed. Detailed microscopic observations show that the main fractures are tortuous and are accompanied by many thinner ramified fractures. Additionally, fractured regions where the resin penetrates significantly are observed around the main fractures in the specimens fractured by the resin B. These induced fractures and fractured regions are considered to be the stimulated region in which permeability is improved. The necessity of estimation on the features of fracture tortuosity and ramified fractures is indicated for more accurate understanding of the well production and the stimulated reservoir volume.